E-Commerce and Web Technologies 7th International Conference, EC-Web 2006, Krakow, Poland, September 5-7, 2006, Proceedings - Bauknecht, Kurt; Pröll, Birgit; Werthner, Hannes (Information Systems and Applications, incl. Internet/Web, and HCI, 2006)
We welcome you to the 7th International Conference on E-commerce and Web Technologies (EC-Web 2006) held in Krakow, Poland, in conjunction with DEXA 2006. This conference was organized for the first time in Greenwich, UK, in 2000, and it has been able to attract an increasing number of participants and interest, reflecting the progress made in the field. As in the previous years, EC-Web 2006 served as a forum bringing together researchers from academia and practitioners from industry to discuss the current state of the art in e-commerce and Web technologies. Inspiration and new ideas emerged from intensive discussions that took place during the keynote address, the formal sessions and the social events. The conference attracted 88 paper submissions and each paper was reviewed by three Program Committee members. The Program Committee selected 24 papers for presentation and publication (an acceptance and publication rate of 27%). We have to confess that this task was not that easy due to the high quality of the submitted papers. We would like to express our thanks to our colleagues who helped put together the technical program: the Program Committee members and external reviewers for their timely and rigorous reviews of the papers, and the Organizing Committee for their help in the administrative work and support. We owe special thanks to Gabriela Wagner for her helping hand concerning the administrative and organizational tasks of this conference.